2022
DOI: 10.3390/jof8050492
|View full text |Cite
|
Sign up to set email alerts
|

Four New Highly Oxygenated Eremophilane Sesquiterpenes from an Endophytic Fungus Boeremia exigua Isolated from Fritillaria hupehensis

Abstract: Four new eremophilane-type sesquiterpenes, boeremialanes A–D (1–4) were obtained from solid substrate cultures of Boeremia exigua (Didymellaceae), an endophytic fungus isolated from Fritillaria hupehensis (Liliaceae). Boeremialanes A–C (1–3) are highly oxygenated eremophilanes with a benzoate unit attached at the C-13 position and are rarely found in nature. Their structures and absolute configurations were determined by extensive spectroscopic methods, electronic circular dichroism (ECD), and nuclear magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Eremophilane-type sesquiterpenes, derived from the biosynthetic precursor farnesy diphosphate (FPP), represent a distinct group within the bicyclic sesquiterpene com pound family. These compounds are characterized by their unique irregular bicycli structures, with structural variations primarily arising from various oxidations on the bi cyclic skeleton and the isopropyl side chain [93]. Related studies have shown that thes compounds displayed anti-inflammatory effects and can inhibit the NO produced by lip opolysaccharide (LPS)-induced RAW 264.7 macrophages [94].…”
Section: Eremophilane-type Sesquiterpenesmentioning
confidence: 99%
“…Eremophilane-type sesquiterpenes, derived from the biosynthetic precursor farnesy diphosphate (FPP), represent a distinct group within the bicyclic sesquiterpene com pound family. These compounds are characterized by their unique irregular bicycli structures, with structural variations primarily arising from various oxidations on the bi cyclic skeleton and the isopropyl side chain [93]. Related studies have shown that thes compounds displayed anti-inflammatory effects and can inhibit the NO produced by lip opolysaccharide (LPS)-induced RAW 264.7 macrophages [94].…”
Section: Eremophilane-type Sesquiterpenesmentioning
confidence: 99%
“…Further studies on endophytic fungi by Ai et al and Yu et al report new eremophilane sesquiterpenoids and new sativene, as well as longifolene sesquiterpenoids plus two new xanthones from Boeremia exigua isolated from Fritillaria hupehensis and the Kiwifruitassociated fungus Bipolaris sp., highlighting the vast chemical diversity to be explored by these plant-associated fungi [51,52].…”
mentioning
confidence: 99%